Simulation of thoracic endovascular aortic repair in a perfused patient-specific model of type B aortic dissection - Mohl, Lukas; Karl, Roger; Hagedorn, Matthias; Runz, Armin; Skornitzke, Stephan; Tölle, Malte; Bergt, Carl Sören; Hatzl, Johannes; Uhl, Christian; Böckler, Dittmar; Meisenbacher, Katrin; Engelhardt, Sandy (International journal of computer assisted radiology and surgery, 2024)
Complicated type B Aortic dissection is a severe aortic pathology that requires treatment through thoracic endovascular aortic repair (TEVAR). During TEVAR a stentgraft is deployed in the aortic lumen in order to restore blood flow. Due to the complicated pathology including an entry, a resulting dissection wall with potentially several re-entries, replicating this structure artificially has proven to be challenging thus far.
Gesehen am 11.11.2024